Lu, Sm, and Y-based double-decker phthalocyanines with enhanced photodynamic therapy performance - Zeki, Ketrin; Yabas, Ebru; Erden, Fuat; Salih, Bekir; Canlica, Mevlude (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
This paper focuses on the preparation of 3,5-di-tert-butylphenoxy substituted Lu, Sm, and Y-based double-decker phthalocyanines (Pcs), and investigation of their PDT properties. Briefly, 1,8,15,22-tetra-(3,5-di-tert-butylphenoxy) bisphthalocyanine derivatives (denoted LuPc2-3, SmPc2-4, YPc2-5) were synthesized by a two-step process. First, metal-free 1,8,15,22-tetra-(3,5-di-tert-butylphenoxy)phthalocyanine was prepared by tetramerization of 3,5-di-tert-butylphenoxy phthalonitrile, which is followed by reaction of different lanthanide salts with 1,8,15,22-tetra-(3,5-di-tert-butylphenoxy)bisphthalocyanine. The resultant double-decker Pcs were characterized in detail by UV-Vis, FT-IR, 1H NMR, fluorescence spectroscopy, MALDI-TOF MS, and elemental analysis. Strikingly, we report that double-decker phthalocyanines are not only photostable, but also exhibit relatively high singlet oxygen quantum yields of 0.96 (LuPc2-3), 0.91 (SmPc2-4) 0.87 (YPc2-5) and in THF.
Keywords: Photodynamic therapy; Photosensitizer; Singlet oxygen; Double-decker phthalocyanines; Rare earth metals; EFFICIENT PHOTOSENSITIZERS; ZINC PHTHALOCYANINE; DERIVATIVES; PORPHYRIN; SUBSTITUENTS; STABILITY; GAP; Chemistry; Crystallography